Changes in sleep quality of children with epilepsy and anxiety of their caregivers after COVID-19 infection: a case-series report - Li, Dan; Shi, Yongjing; Wang, Bo; Zhou, Jing; Wang, Xueying; Huang, Shaoping; Yang, Lin (Frontiers in Pediatrics, 2023)
Objective: To evaluate the effects of COVID-19 infection on epileptic seizures, sleep quality, and caregiving anxiety self-rating scales in children with epilepsy, we did this cross-sectional case-control study. Methods: This case-series study used a questionnaire to recruit outpatients and inpatients of children with epilepsy (CWEs) and their caregivers who visited the Pediatric Epilepsy Department of the Second Affiliated Hospital of Xi'an Jiaotong University from January 10 to March 3, 2023. Epilepsy, COVID-19 vaccination, infection, and therapy, and CWE and caregiver demographics were obtained. The Child Sleep Habits Questionnaire (CSHQ) and Caregiver Anxiety Scale (CAS) measured CWE sleep quality and caregiver anxiety. One-way analysis of variance examined CWE sleep and caregiver anxiety risk factors. Results: 312 children were studied. 221 CWEs infected with COVID-19 were the observation group, while 91 were the control group. 134 (42.9%) of 312 cases were female. The course of epilepsy lasted 4.59±3.36 years and the children were 9.30±3.88 years old. 221 of 312 children infected with COVID-19, and all had fever for 1.71±1.13 days. 10 children who were satisfied with controlled seizures for more than a year had relapsed after COVID-19 infection (4.2%), 4 cases (3.6%) had increased seizures, 8 had reduced seizures (7.7%), 17 had no change, and 182 (82.3%) remained seizure-free. The average sleep time of the CWEs was 9.25±1.04 hours with a 37.25±5.19 CSHQ score and with 44 patients (14.1%) having more than 41 points. The average CAS score was 31.49±8.09, and 16 patients (5.13%) scored above 50. CWEs' sleep and caregiver anxiety were unaffected by COVID-19. The control of seizures, age of onset, types of anti-seizure medicines (ASMs), and seizure duration, focal seizure were risk factors affecting sleep quality. Accordingly, the score of CAS was significantly lower when there was more than one caregiver who cared for the CWE，and the scores were higher when the caregiver was a single female parent. Conclusions: COVID-19 infection did not cause an increase in seizures in CWEs, nor did it worsen their sleep quality of them or aggravate the anxiety of their caregivers.